Analysis of the clinical safety of intralesional injection of collagenase Clostridium histolyticum (CCH) for adults with Peyronie's disease (PD). (13th May 2015) - Carson, Culley C.; Sadeghi‐Nejad, Hossein; Tursi, James P.; Smith, Ted M.; Kaufman, Gregory J.; Gilbert, Kimberly; Honig, Stanton C.
<x xml:space="preserve">Abstract</x> Objective To examine the safety of intralesional injection of collagenase Clostridium histolyticum (CCH) for the treatment of Peyronie's disease (PD), using a pooled safety analysis of patients who received at least one dose of CCH in any of six clinical studies. Patients and Methods Patients from six clinical studies, including three randomised, double‐blind, placebo‐controlled studies and three open‐label safety and efficacy studies, were included if they had received at least one dose of 0.58 mg CCH. Adverse events (AEs), including treatment‐emergent AEs, treatment‐related AEs, and serious AEs (SAEs), were characterised. Potential immunogenicity‐related AEs were evaluated through examination of increased anti‐AUX‐I and anti‐AUX‐II antibody levels, AEs, and reported terms possibly associated with immunological or hypersensitivity events. Results Overall, 85.8% of 1 044 pooled patients reported at least one treatment‐related AE. The most frequently reported (≥25.0% of patients) treatment‐related AEs included penile haematoma (82.7% had the verbatim 'penile bruising'), penile pain, and penile swelling. Most patients (75.2%) had mild‐ or moderate‐severity treatment‐related AEs, and 14.2% had no treatment‐related AEs. Nine patients (0.9%) had treatment‐related SAEs: five with penile haematoma and four with corporal rupture. There was no association between AEs and anti‐AUX‐I or anti‐AUX‐II antibody levels across treatment cycles, and no systemic hypersensitivity reactions occurred. Conclusions This pooled safety analysis shows that although non‐serious and serious treatment‐related AEs can occur after CCH treatment for PD, most were non‐serious and the SAEs were manageable. Providers should be prepared to manage possible SAEs.